Quality in practice: implementation of a clinical outcomes registry in regenerative medicine - Jenio, Frank Zackary (Ann Transl Med, 2019)
BACKGROUND: The aim of this didactic article is to describe the implementation of a clinical outcomes registry within a clinical setting for musculoskeletal regenerative medicine. A patient-centred clinical registry, designed and implemented into the practice of a musculoskeletal clinic specializing in regenerative medicine. METHODS: A focus on patient outcomes at all levels of the patient journey was established to monitor and continually improve care. The registry was designed to monitor the diagnosis, treatment and outcomes of musculoskeletal pathologies of the shoulder, elbow, hip, knee, foot and spine presenting to the clinic. Specifically, the registry was designed for surveillance, tracking, and reporting of efficacy and adverse events of cellular-based therapies. RESULTS: The registry has completed its implementation phase and is now in a pilot period to confirm data collection processes and user feedback. Initial findings indicate suboptimal data entry compliance in key areas that were rectified by refining data fields, reimaging within existing operating systems, and linkage to external supporting documents. CONCLUSIONS: The key impacts of the registry implementation have been to (I) redefine criteria for treatment success and failure within the area of biologic treatments in musculoskeletal practice; (II) instigate discussion, and document standardized treatment pathways, clinical handover processes and shared decision-making with patients; and (III) act as a catalyst to target deficiencies in staff knowledge and skills in the areas of patient management and interaction, clinical documentation and administration processes. A practice registry provides a platform for monitoring treatment safety and efficacy in the context of biologic therapies in musculoskeletal medicine. Registries of this kind will contribute to ongoing discourse regarding best value treatments in the musculoskeletal context.